Efficacy and Safety of Low-Dose Ipragliflozin, a Selective Sodium Glucose Transporter 2 Inhibitor, in Patients with Type 2 Diabetes Mellitus - Ichiro Abe (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Few studies have focused on the efficacy and safety of low-dose of selective sodium glucose transporter 2 (SGLT2) inhibitors in patients with type 2 diabetes. Ipragliflogin is an SGLT2 inhibitor licensed in Japan for administration at standard (50mg/day) or high (100mg/day) doses to treat type 2 diabetes mellitus in Japan. However, little is known about low-dose ipragliflozin (25mg/day) on safety and efficacy on the glucose control parameters and the other metabolic parameters. We study the efficacy and safety of low-dose ipragliflozin for the treatment of diabetic patients. Methods 14 individuals with type 2 diabetes mellitus who had not used SGLT2 inhibitors were recruited and given low-dose ipragliflozin (25mg/day). After 24 weeks, glucose control parameters and the other metabolic parameters were evaluated. Results All patients completed the study without any complications. Compared to baseline, HbA1c, fasting glucose, and HOMA ? significantly improved, and in terms of metabolic parameters, body weight, systolic blood pressure, LDL cholesterol, and BNP significantly improved. In addition, urinary albumin excretion significantly reduced among the patients with microalbuminuria, and for one patient with macroalbuminuria, urinary albumin excretion decreased to half compared to baseline. Conclusion Low-dose ipragliflozin (25mg/day) is useful for treatment for type 2 diabetes mellitus on not only glycemic control but also the other metabolic disorders without complications of SGLT2 inhibitors.